Impact of an educational program on knowledge and quality of life among hemodialysis patients in Khartoum state - Hammad Ali Fadlalmola; Eltayeb Mohammed Awad Elkareem (Elsevier, 2020)
Purpose: The purpose of this study was to evaluate the effectiveness of an educational program on the knowledge and quality of life among hemodialysis patients in Khartoum state. Methods: This study was a hospital-based quasi-experimental study with a pre- and posttest design; conducted among patients in hemodialysis units. Results: The results revealed that there was a significant increase in the overall mean.knowledge from 48.6% pre-intervention to 86.3% post-intervention.of the program, thus improving the quality of life after its implementation. Specifically, the results revealed that there was a significant improvement in all domains of quality of life. Conclusions: The educational program was proven to be effective in improving the knowledge of hemodialysis and the quality of life of patients receiving hemodialysis. The implementation of the educational program had a positive effect on the patients' overall knowledge regarding the concept of hemodialysis, vascular access care, complications, the dietary restrictions, fluids restrictions, types of medications and activities that can help the patients to adapt with disease and hemodialysis.